2010
DOI: 10.1007/s00066-010-2072-y
|View full text |Cite
|
Sign up to set email alerts
|

Stereotactic Body Radiotherapy for Lung Tumors at the Pulmonary Hilum

Abstract: SBRT for lung tumors located in the pulmonary hilar region may be tolerable and acceptable, if multiple treatments to the same major bronchus are avoided, and irradiated volumes are carefully taken into consideration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(25 citation statements)
references
References 35 publications
0
24
1
Order By: Relevance
“…In reports on SBRT of centrally located tumors, on the other hand, 2-year LCR ranges from 60 (29) to 94% (30). This is thought to be related to the lower BED 10 used to avoid severe AEs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In reports on SBRT of centrally located tumors, on the other hand, 2-year LCR ranges from 60 (29) to 94% (30). This is thought to be related to the lower BED 10 used to avoid severe AEs.…”
Section: Discussionmentioning
confidence: 99%
“…Andratschke et al reported a 3-year LCR of 64%, and OS of 29% (32). Oshiro et al reported a 2-year LCR of 60% with BED 10 =80 Gy (29), and Bradley et al reported an 86% 2-year LCR, and 75% 2-year OS with BED 10 =86 Gy (33). As for reports of ≥100 Gy, Timmerman et al reported a 2-year LCR of 95% using a regimen of 60–66 Gy in 3 fr (13), and Rowe et al reported a 2-year LCR of 94% with a BED 10 ≥100 Gy, and 80% when BED 10 <100 Gy, (P=0.02) (34).…”
Section: Discussionmentioning
confidence: 99%
“…9,36,[50][51][52][53]56,57,[59][60][61][62][63][64][65][66][67][68][69][70][71][72][73][74][75] In terms of tumour dose, the LungTech protocol will investigate a medium hypofractionated approach, applying 8.0 3 7.5 Gy to a total dose of 60 Gy; this is equal to a BED of 105 Gy (a/b 5 10). Referring to report 83 of the International Commission on Radiation Units and Measurements (ICRU), 95% of the PTV has to receive at least the nominal fraction dose, and 99% of the PTV receives a minimum of 90% of the nominal dose.…”
Section: Prescribed Dose Normal Tissue Constraintsmentioning
confidence: 99%
“…For normal tissues, the use of a high dose per fraction rather than a conventional fractionated dose can increase the risk of late complications if the same volume were irradiated [67]. To date, only a few studies have reported on the safety and efficacy of treating centrally located lung tumors with SBRT [6870]. In a group of 63 patients with centrally located lung tumors, Haasbeek et al reported that a total of seven patients developed grade 3 acute or late toxicity after undergoing eight fractions of 7.5 Gy [71].…”
Section: Resultsmentioning
confidence: 99%